2017
DOI: 10.1371/journal.pone.0175995
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of an EaZIP gene devoid of transit peptide sequence induced leaf variegation in tobacco

Abstract: Leaf variegation is an ornamental trait that is not only biologically but also economically important. In our previous study, a Mg-protoporphyrin IX monomethyl ester cyclase homologue, EaZIP (Epipremnum aureum leucine zipper) was found to be associated with leaf variegation in Epipremnum aureum (Linden & Andre) G.S. Bunting. The protein product of this nuclear-encoded gene is targeted back to chloroplast involving in chlorophyll biosynthesis. Based on a web-based homology analysis, the EaZIP was found to lack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…The presence and expression of EaZIP were confirmed in all selected seven lines ( Figures 3C,D ). The finding that overexpressing EaZIP was unable to restore the chlorophyll production complements with our previous study that overexpressing the EaZIP caused normal green tobacco plants to become variegated ( Guan et al, 2017 ). The results from these two studies implied that the cloned EaZIP might be defective.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The presence and expression of EaZIP were confirmed in all selected seven lines ( Figures 3C,D ). The finding that overexpressing EaZIP was unable to restore the chlorophyll production complements with our previous study that overexpressing the EaZIP caused normal green tobacco plants to become variegated ( Guan et al, 2017 ). The results from these two studies implied that the cloned EaZIP might be defective.…”
Section: Resultssupporting
confidence: 87%
“…Our previous cloning effort obtained an EaZIP from green pothos (Hung et al, 2010), which lacks a sequence region encoding a N-terminal chloroplast transit peptide (cTP). When overexpressing the cloned EaZIP in wild type tobacco plants which carry the NtZIP also lacking 5 -end sequence coding for a cTP (Liu et al, 2004), surprisingly we found transgenic plants showing variegated phenotype (Guan et al, 2017). However, whether the cloned EaZIP is a functional version or not has not been tested.…”
Section: Overexpressing Eazip Did Not Change the Albino Phenotypementioning
confidence: 83%
See 1 more Smart Citation
“…Specifically, mutations leading to variegation, due to their unique feature of exhibiting both normal and defective plastids in different sectors of the same tissue, are of great interest to research toward understanding (1) chloroplast biogenesis, (2) cross-communication between the nucleus and the other DNAcontaining compartments such as plastids and mitochondria, and (3) the molecular mechanism of variegation. Genes involved in the variegation pattern formation have been cloned in monocot and dicot species (Wu et al, 1999;Chen et al, 2000;Takechi et al, 2000;Prikryl et al, 2008;Hayashi-Tsugane et al, 2014;Wang et al, 2016;Zheng et al, 2016;Guan et al, 2017;Zagari et al, 2017). Despite the advances of identifying the underlying genes, insights into the molecular mechanisms controlling the phenomenon are rare (Sakamoto, 2003;Yu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Genes involved in the variegation pattern formation have been cloned in monocot and dicot species (e.g. Wu et al, 1999; Chen et al, 2000; Takechi et al, 2000; Prikryl et al, 2008; Hayashi-Tsugane et al, 2014; Wang et al, 2016; Zheng et al, 2016; Guan et al, 2017; Zagari et al, 2017). Despite the advances of identifying the underlying genes, insights to the molecular mechanisms controlling the phenomenon are rare (Sakamoto, 2003; Yu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%